Dissemination and Implementation of Evidence-Based Falls Prevention Programs: Reach and Effectiveness. Issue 1 (9th July 2021) - Brach, Jennifer S; Juarez, Gardenia; Perera, Subashan; Cameron, Kathleen; Vincenzo, Jennifer L; Tripken, Jennifer
Abstract: Background: Using the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework, we describe the implementation of evidence-based fall prevention programs (EBFPPs) by Administration for Community Living grantees during 2014–2019. Method: Forty-four grantees contributed to the national data repository. Data components include workshop information, participant information, attendance records, and organizational data. Data were collected before and after implementation of the EBFPPs. Results: Ten different programs were offered in 35 states with the most common settings being senior centers (25.3%), residential facilities (16.8%), health care organizations (12.5%), and faith-based organizations (11.1%). Individuals who participated in the programs ( N = 85 848) had an age of 75.5 ± 9.7 years and were primarily female (79.7%), and the majority (86.2%) reported at least some fear of falling. At the postprogram assessment, 31.8% reported less fear of falling, 21.6% reported fewer falls, and 10.1% reported fewer injurious falls (all p < .0001). Conclusions: EBFPPs implemented by Administration for Community Living grantees reached over 85 000 older adults. Participation in the EBFPPs resulted in improved confidence, decreased fear of falling, and fewer falls and injurious falls. Future efforts should focus on reaching specific underserved minorities and examining the effectiveness of individual programs.